Single-cell bilayer design of a terahertz six-channel metasurface for simultaneous holographic and grayscale images - Zhiqiang Du; Chunhui Zhu; Zhengyong Song (Scientific Reports, 2025)
Abstract Metasurfaces have exhibited excellent capabilities in controlling main characteristics of electromagnetic fields. Thus, a lot of significant achievements have been attained in many areas especially in the fields of hologram and near-field imaging. However, some of these designs are implemented in a manner of interleaved subarrays that complicates the design and makes them difficult to achieve integration. Here, an innovative stacking technique of metasurface is combined with vanadium dioxide (VO2) to achieve independent imaging of six channels in terahertz band. Our research combines intensity modulation controlled by the Malus’s law and phase modulation of geometry and propagation to merge amplitude, phase, and polarization manipulation of electromagnetic wave. A “six-in-one” meta-device is constructed by combining phase change properties of VO2 to realize simultaneous near-field grayscale imaging and far-field holography. This design has advantages of wide bandwidth and low crosstalk. Based on the advantage of low crosstalk, single-cell bilayer design allows the number of independent channels to be doubled within an acceptable error range. The proposed metasurface introduces a fresh viewpoint for the design of multi-purpose meta-devices, and has broad application prospects in information encryption and multi-channel image display.